The Theological Tendency of 'Alī b. 'Īsā al-Rummānī and Its Manifestations in Rhetorical Theorizing: An Analytical Study on “al-Nukat Fī I'jāz al-Qur`ān” ("النزعة العقائدية لدى علي بن عيسى الرماني وتجلّياتها في التنظير البلاغي: دراسة تحليلية لرسالة "النكت في إعجاز القرآن) - Ahmad Muhdhor; Mohammad Yunus Masrukhin (Buletin Al-Turas, 2026)
Purpose The claim of al-Rummānī’s objectivity on rhetorical theorization is examined in these papers. The two main issues with the study are as follows: In what ways does al-Rummani's rhetorical theorizing in “al-Nukat fī I’jāz al-Qur`ān” reflect his theological inclination? And considering that the two discourses are part of separate frameworks, why are his rhetorical theories based on doctrinal foundations?  Method The first point is addressed by highlighting al-Rummānī’s doctrinal tendency and its crystallization through a relational analysis of his theorization and Mu’tazilite theological doctrines; the second is addressed by attributing the phenomenon to how epistemological texts are generated, based on the authoritative discourse that represents the author’s intellectual world.  Result Al-Rummānī’s theological inclination is evident in his rhetorical theorizing on several phenomena, including his triangulation of the levels of rhetoric based on the principle of the intermediate position, his adaptation of an example of the problem of brevity, his extensive establishment of the theory of metaphor, and his application of exaggeration in accordance with the principle of creating actions.  Conclusion The results disprove the assertion that al-Rummani's rhetorical thinking is objective. This is because the supremacy of theological discourse made it possible to develop rhetorical discourse atop it, but in a different setting. Moreover, the foundation of Arabic rhetoric, the question of inimitability, is a theological matter before it is a literary one